2017
DOI: 10.1097/pec.0000000000001142
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Glucocorticoid Response to Single-Dose Dexamethasone for Croup in Children

Abstract: Objectives Dexamethasone is associated with adrenal insufficiency in adults and children with chronic disease. This association has not been studied after single-dose oral dexamethasone, the standard of care for children with croup. We hypothesized that single-dose oral dexamethasone in children with croup is associated with a transient decrease in endogenous glucocorticoids. Methods We conducted a prospective, 2-arm, pharmacodynamic study of single-dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The number of studies contributing to each meta-analysis ranged from one to seven (range 58–2178 children). There were no statistically significant differences between: (1) systemic corticosteroid compared with placebo for severe infections,30 74 96 99 systemic infections,30 40 43 83 infections of the lung/trachea30 40 54 74 96 98 105 and the upper respiratory tract,30 43 54 65 67 74 and voice complaints43 (estimated pORs between 0.15 and 1.26) and (2) inhaled corticosteroid compared with placebo for severe infections,45 systemic infections,43 45 lung/trachea,45 infections of the upper respiratory tract37 44 45 65–67 or voice complaints37 43 100 101 (estimated pORs between 0.54 and 1.51). No study comparing dexamethasone with another corticosteroid reported infections or respiratory AEs.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The number of studies contributing to each meta-analysis ranged from one to seven (range 58–2178 children). There were no statistically significant differences between: (1) systemic corticosteroid compared with placebo for severe infections,30 74 96 99 systemic infections,30 40 43 83 infections of the lung/trachea30 40 54 74 96 98 105 and the upper respiratory tract,30 43 54 65 67 74 and voice complaints43 (estimated pORs between 0.15 and 1.26) and (2) inhaled corticosteroid compared with placebo for severe infections,45 systemic infections,43 45 lung/trachea,45 infections of the upper respiratory tract37 44 45 65–67 or voice complaints37 43 100 101 (estimated pORs between 0.54 and 1.51). No study comparing dexamethasone with another corticosteroid reported infections or respiratory AEs.…”
Section: Resultsmentioning
confidence: 93%
“…Database and grey literature searches yielded 9134 records. Eighty-six papers (85 studies)23–108 involving 11 505 participants were included (figure 1). Characteristics of the included studies are in online supplementary file 3.…”
Section: Resultsmentioning
confidence: 99%